2020
DOI: 10.21203/rs.3.rs-102674/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between AST to ALT Ratio and Peripheral Artery Disease in Chinese Hypertensive Population: A Cross-Sectional Study

Abstract: Background: Previous studies had shown the role of aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AST/ALT) in cardiovascular disease . Peripheral artery disease(PAD) is an important risk factor for cardiovascular death. However, there are fewer investigations of the correlations between the AST/ALT ratio and Peripheral artery disease (PAD). Methods: We analyzed data of 10,900 hypertensive patients from the Chinese Hypertension Registry Study. Using a multivariate logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this issue of Angiology, Liu et al 1 examine the association between the aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio and the prevalence of peripheral arterial disease (PAD) in participants of the Chinese Hypertension Registry Study (n ¼ 10 900 patients with hypertension, mean age 63.86 + 9.25 years, 47.06% male). Using the anklebrachial index as an indicator of the presence of arterial insufficiency, the authors 1 identified 350 patients with PAD (prevalence: 3.21%).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In this issue of Angiology, Liu et al 1 examine the association between the aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio and the prevalence of peripheral arterial disease (PAD) in participants of the Chinese Hypertension Registry Study (n ¼ 10 900 patients with hypertension, mean age 63.86 + 9.25 years, 47.06% male). Using the anklebrachial index as an indicator of the presence of arterial insufficiency, the authors 1 identified 350 patients with PAD (prevalence: 3.21%).…”
mentioning
confidence: 99%
“…The authors 1 observed that the AST/ALT ratio was positively and independently associated with the risk of PAD (odds ratio [OR]: 1.31, 95% CI: 1.13-1.59), noting a significant increased risk of PAD for those in T3 versus T1 (OR: 1.49, 95% CI: 1.09-2.04, P ¼ .005); by combining T1 and T2 (as a single reference group), the risk of PAD was positively associated with higher AST/ALT ratio, yielding a risk ratio of 1.52 (95% CI: 1.20-1.95). 1 They 1 concluded that an AST/ALT ratio !1.65 is associated with PAD risk and that it could help identify patients at high risk of vascular events.…”
mentioning
confidence: 99%
See 2 more Smart Citations